Never give up : my life in the wild - Grylls, Bear (Washington : National Geographic, 2022)
"Admired by millions as the star of Man vs. Wild and the acclaimed NGC series Running Wild, global adventurer Bear Grylls has explored places few would dare to go. Now, he shares time-honored lessons for leading an adventurous life through stories drawn from his personal experiences, as well as encounters with a diverse group of celebrities who have participated in his wildly popular television shows. In these inspiring pages, Grylls chronicles his life since stepping onto the small screen, taking readers on his most famous adventures, sharing stories from his favorite expeditions, and capturing his hairiest survival challenges. The followup to the internationally best-selling Mud, Sweat and Tears, this new autobiography goes behind the scenes on infamous Man vs. Wild shoots and provides an insight into what it's really like to "Run Wild" with guests including President Obama, Roger Federer, and Julia Roberts. Along the way, Bear explores the valuable lessons he's learned in the wild, opens up about his most personal challenges and achievements, and celebrates the true value of adventure and the enduring importance of courage, kindness, and resilience. Written for outdoor enthusiasts and armchair adventurers alike, Never Give Up offers an inspiring path to help readers live their best lives"--
Keywords: Grylls, Bear; Wilderness survival; Mountaineers